Vitamin D status and risk of rheumatoid arthritis: systematic review and meta-analysis - Joanna L. Clasen; Rachel Cole; Dagfinn Aune; Edward Sellon; Alicia K. Heath (BMC Rheumatology, 2023)
Abstract Background Vitamin D is important for immunomodulation and may play a role in autoimmune diseases. Studies have reported a high prevalence of vitamin D deficiency in rheumatoid arthritis (RA) patients, and vitamin D status, assessed by circulating 25-hydroxyvitamin D [25(OH)D] concentration, is inversely associated with RA disease activity. However, it is unclear whether vitamin D deficiency increases the risk of later developing RA. We conducted a systematic review and meta-analysis of pre-diagnostic 25(OH)D concentrations and risk of RA. Methods Medline and Embase databases were searched in December 2021 using various keywords for ‘vitamin D’, ‘rheumatoid arthritis’, and ‘prospective study’. Publications identified from the search were screened for eligibility, studies were excluded if vitamin D status was measured at or after RA diagnosis, and data were extracted from relevant articles. Bayesian meta-analysis was used to estimate the summary relative risk (RR) and 95% credible interval (CrI) for risk of RA in relation to circulating 25(OH)D concentrations, as well as the between-study heterogeneity. Results The search strategy yielded 908 records, of which 4 publications reporting on 7 studies, involving a total of 15,604 participants and 1049 incident RA cases, were included in the meta-analysis. There was no suggestion of an association between 25(OH)D concentration and subsequent risk of RA. The pooled RR per 25 nmol/L increment in 25(OH)D was 0.96 (95% CrI 0.82–1.13; I 2 = 52%). No associations were evident in men (RR = 1.02, 95% CrI 0.65–1.61; I 2 = 77%, 2 studies) or women (RR = 0.94, 95% CrI 0.73–1.22; I 2 = 71%, 4 studies). Conclusions This systematic review and meta-analysis did not identify evidence of an association between 25(OH)D and RA risk, but there was notable between-study heterogeneity and a lack of precision. Investigations in large-scale prospective studies with long follow-up or suitably designed Mendelian randomisation studies with consideration of potential non-linear relationships are needed to determine whether vitamin D is involved in RA aetiology.